A Story of Readers’ Characteristics and Text Preferences in Reading Time - Mega Mulianing Maharani; Abdurrachman Faridi; Dwi Rukmini; Sri Wuli Fitriati (Universitas Negeri Semarang, 2022)
Abstract. This qualitative study investigated 20 students as readers on a certain university in Semarang who joined reading class at a certain semester. The purpose of the study was to share the readers’ characteristics and their text preferences in reading time. The researchers examined the readers’ characteristics (socio-economic status and gender) and text preferences (animation, non-animation, printed and digital) used in accompanying their reading time. Female and male students who came from different socio-economic status read differently in their reading time. They had different preferences in choosing text. Female and male students had different preferences in choosing animation and non-animation texts. Printed and digital texts were also classified to be different choice for female and male students. Implications include how to mediate students with the most dominant text preferences in facilitating their reading time. The text selection can accommodate the success of reading activities.